Midwives‘ professional identity: Lithuanian situation - Vaičienė, Vita (Slauga. Mokslas ir praktika, 2023)
The profession of midwife is one of the oldest in the world and is considered prestigious because of the characteristics of midwifery practice. The ability to reject or control stress is the result of the personal life and personality formation of everyone who is exposed to various sources of stress or stressors. Occupational burnout is less common in psychologically strong people who are communicative, flexible to different situations, feel empathy, have excellent problem solving, have internal control, and feel self-esteem.The aim. To evaluate expressiveness of midwives‘ professional resilience.Methods. The cross-sectional study was done. Study was conducted by questionnaire survey. The study involved 338 midwives from whole Lithuania Obstetrics wards. Statistical data analysis performed by using SPSS 23.0 program. Percentages, frequencies, averages and standard deviations were calculated. Relevant statistics were calculated based on T-test and correlation coefficient. Results were statistically significant when p
Keywords: midwife; professional identity; depression-anxiety-stress scale; Copenhagen burnout inventory